2020
DOI: 10.1051/sicotj/2020010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term performance of oxidized zirconium on conventional and highly cross-linked polyethylene in total hip arthroplasty

Abstract: Introduction: Polyethylene wear and subsequent osteolysis remain obstacles to the long-term survivorship of total hip arthroplasty (THA). Highly cross-linked polyethylene (XLPE) with radical quenching represents a massive leap forward with dramatically improved wear rates compared to ultra-high molecular weight polyethylene (UHMWPE). In this study we evaluate the wear of UHMWPE and XLPE coupled with oxidized zirconium (OxZr) femoral heads. Methods: A longitudinal, retrospective analysis was performed identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Despite the fact that many studies have proven in vivo mid-and long-term efficacy of OFH in total hip arthroplasty in reducing linear and volumetric wear and osteolysis, [3][4][5]17 with even reduced polyethylene wear 8 in vitro; this may be not the case if any surface damage occurs to OFH, especially after dislocation/reduction when contact with the metal cup may occur. During the primary surgery, if an OFH is planned for use, careful component alignment and insertion procedure should be utilized, and vigilant reduction technique should be used to avoid any surface damage to the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that many studies have proven in vivo mid-and long-term efficacy of OFH in total hip arthroplasty in reducing linear and volumetric wear and osteolysis, [3][4][5]17 with even reduced polyethylene wear 8 in vitro; this may be not the case if any surface damage occurs to OFH, especially after dislocation/reduction when contact with the metal cup may occur. During the primary surgery, if an OFH is planned for use, careful component alignment and insertion procedure should be utilized, and vigilant reduction technique should be used to avoid any surface damage to the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found mean wear rates for XLPE were towards the more favourable end of the range of 0.02 mm/year to 0.07 mm/year wear rates in previous studies. 4,7,10,13,22-2431-35 This may be attributable to our study using first-year radiographs as reference films to allow for creep deformation, excluding patients undergoing revision surgery from the final wear analysis, and using a standardized surgical technique in all patients to limit confounders such as acetabular component design, polyethylene geometry, femoral head diameter, femoral head geometry, and stem design. Roedel et al 4 reviewed outcomes in 87 patients aged under 50 years undergoing THA with XLPE, and reported that the mean polyethylene liner wear rate was 0.04 mm/year at 15 years’ follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other laboratory-based studies and clinical trials have reported on the wear characteristics of these bearing surfaces, but there remains a paucity of prospective RCTs reporting on validated clinical outcomes, polyethylene wear rates, and risk of osteolysis with long-term follow-up. 3,4,13,21-24…”
Section: Introductionmentioning
confidence: 99%
“…We are not aware of other RSA studies that have compared the wear rate of XLPE between the initial 5-year period and the subsequent 5 years, when oxidation and mechanical change could affect wear rates. NonRSA studies demonstrated sustained low wear rates beyond 10 years and a continued absence of wear-induced lysis [2,13,23,31], but lacked the sensitivity to compare wear rates over time. Our RSA wear measurements demonstrated a stable wear pattern with no evidence of increasing wear after 5 years in situ, and we found that no individual exceeded 0.025 mm/year proximal wear in either the first or second 5-year periods.…”
Section: Change In Wear Between 5 and 10 Yearsmentioning
confidence: 99%